PBL Application To Improve Understand Concepts Evaluation Educational 2017/2018 - Pradipta, Anangga Widya (Universitas Nusantara PGRI Kediri, 2018)
This study aims to improve the understanding of the concept of Educational Evaluation through the implementation of PBL (Problem-based learning),. This type of research is a classroom action research that includes 4 steps of activities in 1 cycle of planning, action, observation and reflection. The research subjects are and lecturers in the fourth semester of academic year 2016/2017. All are given action using PBL (Problem-based learning). Data collection techniques used were interviews, observations, and tests. The results of this study indicate that the use of PBL (Problem-based learning) can improve the understanding of the concept of PJKR IKIP Budi Utomo Malang up to very good criteria in cycle III. Aspects of student concept comprehension increase from the average pre-action score of 56 to 84.